Evaluating the Cool Versus Not Cool Procedure via Telehealth - Cihon, Joseph H. (Behav Anal Pract, 2021)
Autistics/individuals diagnosed with autism spectrum disorder (ASD) commonly display qualitative impairments in social behavior that commonly result in the use of interventions directly targeting the development of social skills. The COVID-19 pandemic has highlighted the need for effective social skills interventions that can be delivered directly via telehealth. The Cool Versus Not Cool procedure has continually been documented as effective within the literature. However, its reported use has been limited to in-person delivery. The purpose of this study was to evaluate the effectiveness of the Cool Versus Not Cool procedure conducted via telehealth to teach three children diagnosed with ASD to change the conversation when someone is bored. The results of a nonconcurrent multiple-baseline across-participants design demonstrated that all three participants reached the mastery criterion in four to eight sessions. Responding generalized to another adult for two of the three participants, and all three participants maintained correct responding. Social validity measures indicated the skill was important to teach, the intervention was acceptable and effective, and the telehealth format was an acceptable replacement for in-person intervention for these three participants.